Identification and enzymatic profile of yeasts isolated from artisinal cheese in Southern Brazil - Landell, Melissa Fontes; Hartfelder, Claudia; Valente, Patrícia (Acta Scientiae Veterinariae, 2018)
Yeasts may contribute positively to the characteristic taste and flavour development during cheese ripening or cause deterioration of the product. In this study we report the presence of yeasts in 59 samples of artisanal cheeses (43 samples of colonial cheese, 5 of ricotta, 9 of provolone, and 2 of Caccio Cavallo) marketed at stands in the coastal area of Rio Grande do Sul, collected between November 2004 and June 2005. Yeast counts were between 10 4 and 107 UFC/g. One hundred and ten strains were isolated from 30 representative cheese samples. Of these, 97 isolates had ascomycetic affinity, and only 13 were basidiomycetes. The isolates belong to the genera Candida, Debaryomyces, Dekkera, Dipodascus, Galactomyces, Kluyveromyces, Kodamaea, Pichia, Rhodosporidium, Saccharomyces, Schizoblastosporion, Sporidiobolus, Torulaspora, Trichosporon, Yarrowia, and Zygosaccharomyces. The predominant species found were Yarrowia lipolytica, Debaryomyces hansenii, and Candida zeylanoides. More than 56% of the strains were lipolytic, while almost 13% were caseinolytic, and approximately 31% were gelatinolytic. The presence of potentially pathogenic and/or deteriorating yeasts emphasizes the need for a better hygienic control of cheese manufacturing and storage. The ability these microorganisms have to produce proteolytic and lipolytic enzymes enhance the potential risk of cheese deterioration during storage.